Spillovers from High-Skill Consumption to Low-Skill Labor Markets - Mazzolari, Francesca; Ragusa, Giuseppe (The Review of Economics and Statistics, 2013)
The least-skilled workforce in the United States is disproportionally employed in the provision of time-intensive services that can be thought of as market substitutes for home production activities. At the same time, skilled workers, with their high opportunity cost of time, spend a larger fraction of their budget in these services. Given the skill asymmetry between consumers and providers in this market, product demand shifts—such as those arising when relative skilled wages increase—should boost relative labor demand for the least-skilled workforce. We estimate that this channel may explain one-third of the growth of employment of noncollege workers in low-skill services in the 1990s.